Investigating the impact of extraneous distractions on consultations in general practice: Lessons learned - Spilsbury Katrina; O'Shea Carolyn; Arnet Hayley; McKinley Robert; Jiwa Moyez; Smith Marthe (BMC Medical Research Methodology, 2009)
Abstract Background Extraneous distractions may influence the flow of general practice consultations. This study piloted a methodology to examine the impact of interrupting general practitioners (GPs) while consulting actor-patients. Methods Six GPs were video recorded consulting six actor-patients each presenting a different clinical scenario in a simulated surgery. Five cases presented red flag cancer symptoms. Half the consultations were interrupted. Two independent assessors, blinded to the occurrence of interruptions, assessed consultation performance using the Leicester Assessment Package (LAP) for clinical competence. Results 24 of 36 consultations were video recorded with sufficient audio-visual clarity to allow scoring. The association between LAP score and three variables could be studied: a variety of interruptions, different GPs and various scenarios. Agreement between assessors on GP performance was poor and showed an increased bias with increasing LAP score. Despite this, the interruption did not significantly impact on assessor LAP scores (Mean difference: 0.22, P = 0.83) even after controlling for assessor, different GPs and scenarios. Conclusion Extraneous distractions had no impact on GP performance in this underpowered pilot study, a conclusion which needs to be confirmed in a larger study. However several important lessons were learned. Recorded actor-patient clinical sessions are logistically challenging. GPs whose skills were not previously assessed were working in unfamiliar surroundings dealing with relatively straight forward diagnostic challenges and may have anticipated the interruptions. In a redesign of this experiment it may be possible to eliminate some of these limitations.